Šesta brzina - Šotra, Zdravko (Yugoslavia : Avala Film Beograd ; CFS Koštunjak Beograd, 1981)
This light comedy, set in Yugoslavia of the late 1970s, revolves around various episodes in the life of middle-aged car mechanic Života. Easygoing and never in a hurry, Života runs his workshop in the in a very different way to his rival across the street, a swift businessman always busy servicing cars, but nothing more. Života is the opposite: in the setting of his workshop and the adjoining yard, his customers bring along their different life troubles as well. On and on, Života gets openheartedly involved in relationships with his lively customers, from a car hypochondriac utterly convinced that there is something wrong with his perfect new car to a pensioner who tries to turn his old car into suitable living quarters and thus make up for the lack of space in his small apartment. Regardless of what they are, Života tries to help them solve their private problems and in the process gets himself into some comical and sad adventures. Inevitably, times change and eventually, not without bitterness, he tries to change himself, intending to become more like his colleague across the street. But people need him the way he is and miss his closeness and warmth, and soon Života is his old self again.
Keywords: Fiction films